Bone Texture Fractal Dimension Analysis of Ultrasound-Treated Bone around Implant Site: A Double-Blind Clinical Trial - Elaf Akram Abdulhameed; Natheer Hashim Al-Rawi; Asmaa Tahseen Uthman; Ab Rani Samsudin (Hindawi Limited, 2018)
Objectives. To evaluate the efficacy of bone texture fractal dimension (FD) analysis method in predicting implant stability from intraoral periapical radiographs using two implant protocols. Materials and Methods. A double-blind clinical trial was conducted on 22 subjects who needed dental implants. The participants were randomized into two groups, the control group with standard implant protocol treatment and the intervention group with added low-intensity power ultrasound treatment (LIPUS) besides the standard implant protocol. The FD values of bone density were carried out on the mesial and distal sides of the implant on digital intraoral radiographs using the box-counting method. Both resonance frequency (RF) and fractal dimension (FD) were assessed in three time intervals: after surgery and before and after loading. Results. FD on both the mesial and distal sides serve as very good-to-excellent tests with high validity (ROC area exceeding 0.8) in predicting high implant stability (ISQ ≥ 70). The mesial side measurements were consistently better than the distal side among the intervention groups. The optimum cutoff value for the FD-mesial side that predicts a highly stable implant (ISQ ≥ 70) is ≥1.505. At this optimum cutoff value, the mesial side FD is associated with a perfect sensitivity (100%) and fairly high specificity (86.5%). Conclusion. The FD analysis could be recommended as an adjunctive quantitative method in prediction of the implant stability with very high sensitivity and specificity. This trial is registered with ISRCTN72648040.